Perspectives on the underlying drivers of urgent and emergency care reconfiguration in Ireland. (26th October 2017) - Droog, E.; Foley, C.; Healy, O.; Buckley, C.; Boyce, M.; McHugh, S.; Browne, J.P.
Summary: Background: There is an increasing tendency to reconfigure acute hospital care towards a more centralised and specialised model, particularly for complex care conditions. Although centralisation is presented as "evidence‐based", the relevant studies are often challenged by groups which hold perspectives and values beyond those implicit in the literature. This study investigated stakeholder perspectives on the rationale for the reconfiguration of urgent and emergency care in Ireland. Specifically, it considered the hypothesis that individuals from different stakeholder groups would endorse different positions in relation to the motivation for, and goals of, reconfiguration. Methods: Documentary analysis of policy documents was used to identify official justifications for change. Semi‐structured interviews with 175 purposively sampled stakeholders explored their perspectives on the rationale for reconfiguration. Results: While there was some within‐group variation, internal and external stakeholders generally vocalised different lines of argument. Clinicians and management in the internal stakeholder group proposed arguments in favour of reconfiguration based on efficiency and safety claims. External stakeholders, including hospital campaigners and local political representatives expressed arguments that focused on access to care. A "voter" argument, focused on the role of local politicians in determining the outcome of reconfiguration planning, was mentioned by both internal and external stakeholders, often in a critical fashion. Conclusion: Our study adds to an emerging literature on the interaction between a technocratic approach to health system planning advocated by clinicians and health service managers, and the experiential "non‐expert" claims of the public and patients.